Contemporary perspectives on the ecological impacts of invasive freshwater fishes - Britton, John Robert (Journal of fish biology, 2023)
Introductions of non‐native freshwater fish continue to increase globally, although only a small proportion of these introductions will result in an invasion. These invasive populations can cause ecological impacts in the receiving ecosystem through processes including increased competition and predation pressure, genetic introgression and the transmission of non‐native pathogens. Definitions of ecological impact emphasize that shifts in the strength of these processes are insufficient for characterizing impact alone and, instead, must be associated with a quantifiable decline of biological and/or genetic diversity and lead to a measurable loss of diversity or change in ecosystem functioning. Assessments of ecological impact should thus consider the multiple processes and effects that potentially occur from invasive fish populations where, for example, impacts of invasive common carp Cyprinus carpio populations are through a combination of bottom‐up and top‐down processes that, in entirety, cause shifts in lake stable states and decreased species richness and/or abundances in the biotic communities. Such far‐reaching ecological impacts also align to contemporary definitions of ecosystem collapse, given they involve substantial and persistent declines in biodiversity and ecosystem functions that cannot be recovered unaided. Thus, while not all introduced freshwater fishes will become invasive, those species that do develop invasive populations can cause substantial ecological impacts, where some of the impacts on biodiversity and ecosystem functioning might be sufficiently harmful to be considered as contributing to ecosystem collapse.